Adiksi Kafein: Pengaruh Kebiasaan Mengkonsumsi Minuman Berkafein pada Siswa Kelas XII di MA At-Taqwa Cihampelas - F.M, Naila Aurhelia; Sari, Resti Okta (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Coffee is one of the drinks that contain caffeine and is favored by various groups including teenagers and children. This study aims to determine how the influence of the habit of consuming caffeinated drinks on class XII students at MA At-Taqwa Cihampelas. In this study using the observation method, and systematic literature review by searching and collecting library data via the internet which aims to identify the influence and impact of consuming caffeinated drinks excessively, and also identify how students' insights and understanding of the dangers of caffeine addiction. The results of the study show that there are 2 students who can be said to be addicted to caffeine, which is known through classical guidance in the brainstorming session and shows a lack of insight into the negative effects that can be felt when addicted to caffeine.